CUSTOMER RELATIONSHIP MANAGEMENT PT. SAMSUNG ELECTRONICS INDONESIA DI TENGAH PANDEMI COVID-19 DI INDONESIA - Wahdian -; Sri Dwi Setiawati (Linimasa : Jurnal Ilmu Komunikasi, 2020)
ABSTRACT Samsung Indonesia as one of the big companies affected by the covid-19 phenomenon approached customer relationship management approach by making the program "Samsung Near the Heart" and "Pick Up Service" through three components, namely people, processes and technology. PT. Samsung Indonesia succeeded in building relationships with consumers and became the No. 1 Top Brand Smartphone. 1 of 2020 in Indonesia, amid the Covid-19 pandemic. The purpose of this research is to find out Samsung's efforts in building relationships with customers, especially in Indonesia. This study uses a qualitative case study method with data collection techniques from interviews, observations and documentation. The results of this study note that PT. Samsung Indonesia in an effort to build relationships with customers through the Customer Relationship Management approach is carried out through employees and technological processes, namely the use of official websites, the use of the Whatsapp and Instagram applications as the main social media in providing information to build relationships with consumers and conducting online advertising through Instagram Ads and Facebook Ads.